2018
DOI: 10.1007/s40822-018-0117-1
|View full text |Cite
|
Sign up to set email alerts
|

Informal employment in Kazakhstan: a blessing in disguise?

Abstract: Informality is heterogeneous, dynamic and difficult to quantify; the formal-informal gap in earnings is one major component of it that we wish to examine. Using the 2013 Kazakhstan Labour Force Survey (KLFS), we analyse the returns that formal and informal workers receive for a given set of characteristics and also use a matching technique to decompose the gap. We observe that in Kazakhstan there is a substantial earnings gap in favour of formal workers and that a quarter of the gap remains unexplained. Our st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Kazakh authors reveal the problems of the labor market, but the topic of freelancing remains underexplored. (Tolepbergen, 2022;Mussurov et al, 2019) In general, freelancing in the CIS is actively explored by Higher School of Economics (HSE University) scientists A. Shevchuk and D. Strebkov. In one of their latest works, they point out how the Russian language and specific socio-economic factors facilitate a distinct online labor market that operates across the vast territory of the former Soviet Union and beyond (Shevchuk et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Kazakh authors reveal the problems of the labor market, but the topic of freelancing remains underexplored. (Tolepbergen, 2022;Mussurov et al, 2019) In general, freelancing in the CIS is actively explored by Higher School of Economics (HSE University) scientists A. Shevchuk and D. Strebkov. In one of their latest works, they point out how the Russian language and specific socio-economic factors facilitate a distinct online labor market that operates across the vast territory of the former Soviet Union and beyond (Shevchuk et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…While classified as a middle-income country, this status does not fully capture the socioeconomic realities of Kazakhstan. Informality clearly stands out as a dominant approach: approximately 2.9 million of Kazakhstan's 8.5 million workers engage in informal employment, with 77% of them being paid employees in registered businesses (Mussurov et al, 2019). In the significant SME sector (accounting for 96.7% of all firms and employing 37.5% of the workforce, OECD, 2020) approximately 40% of formal enterprises compete with informal sector counterparts, viewing this competition as a barrier to their operations (EBRD, 2020).…”
Section: Context and Theoretical Background 21 The Kazakhstani Contextmentioning
confidence: 99%
“…While classified as a middle-income country, this status does not fully capture the socioeconomic realities of Kazakhstan. Informality clearly stands out as a dominant approach: approximately 2.9 million of Kazakhstan's 8.5 million workers engage in informal employment, with 77% of them being paid employees in registered businesses (Mussurov et al. , 2019).…”
Section: Context and Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…In this view, the study conducted by PricewaterhouseCoopers (2018) found a tight link between the economic prosperity of a state and the occurrence of fraud: for developing countries, 15% of the analyzed financial companies expect an important increase of the invested resources for fraud detection over the next two years, compared to only 9% of the companies from developed countries. The study of Mussurov et al (2019) found that the informal economy characterizes many transition countries belonging to the Eastern part of Europe and to the Central part of Asia. For these countries, they found a percentage that ranges between 20 and 60% of employment to consist of informal jobs.…”
Section: Literature Reviewmentioning
confidence: 99%